Development of Medial Longitudunal Arc in Children Aged 3-10 Years - Duygu Akın Saygın; Huriye Nur Kantar; Meryem Esma Düz; Sevim Akdoğan; Ali Keleş; Mehmet Tuğrul Yılmaz; Neslihan Altuntas Yılmaz (Genel Tıp Dergisi)
Purpose: It is very important to follow the development of the medial arch in children and to detect it in the early period in case of developmental deficiency. The aim of this study is to determine the development of medial arch in children by investigating the change in plantar contact area ratio and pressure with age. Materials and Methods: 51 (16 girls, 35 boys) healthy children (3-10 years old) whose consent was obtained by their families with the randomization method evaluated on the foot sole pressure measuring device were included in our study. For evaluation, medial and lateral of the anterior part of the foot, medial and lateral of the middle part, and medial and lateral of the posterior part of the foot were divided into six. In our study, the ratio of the contact surfaces of the determined areas of the foot to the entire foot sole area and the sole pressure per unit surface were statistically evaluated according to age. The obtained data were analyzed with descriptive statistics and percentage analyzes in the SPSS 11 package program. Results: As a result of the statistical analysis, no statistically significant difference was found between the plantar pressure and contact area ratio values of the right and left foot regions (p>0.05). In the analysis of the plantar pressure value according to age, there was no significant difference between the 9th and 10th ages of 3,4 and 5 years of age only in the medial of the midfoot (p>0.05). In plantar contact area ratios; While there was a significant increase in the medial part of the anterior part of the foot and the lateral part of the posterior part of the foot above the age of 8, there was a significant decrease in the medial part of the middle part of the foot (p<0.05). Conclusion: According to the results we obtained, it was determined that 8 years of age is important in the development of MLA and with the development of the arch, foot contact is transferred from the medial of the anterior part of the foot to the lateral part of the posterior part of the foot.